PEMANFAATAN DATA GEOSPASIAL UNTUK PEMBUATAN PETA DAERAH IRIGASI POMPA III NAGARI SINGKARAK KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Delvi Yanti; M. Agita Tjandra; Mislaini Mislaini; Omil Chamyn Chatib (Jurnal Hilirisasi IPTEKS, 2018)
During the costing system in the irrigation water fee DI Pump III Nagari Singkarak based on the number of seeds used for each field. Inaccurate data makes farmers feel the imbalance between the rights obtained by the obligations to be paid. Whatever as good management but the management is not supported by the data is accurate, then it would not be able to give good results. Irregular landform and stratified into obstacles in getting data that accurately measure land area, but that does not mean the issue can not be resolved, one of which is the application of GIS (Geographic Information System). The method used in this activity is education, measurement, and map-making. Results of the extension activities undertaken are farmers understand the importance of the data base. Measurement of land by the owner or tenant of land is done by using GPS (Global Positioning System). The data obtained from the measurement results in the form of coordinates for each plot of land. Data obtained from field measurements should be transferred from the GPS to ArcGIS 9.x software to do the processing to obtain the land by their respective owners or tilling of the soil. Land area data by their respective owners or tenants the merger for each BSK (Blok Skunder Kwarter), in order to obtain a map of each BSK (BSK I – BSK V). Incoperation whole BSK result Pump Irrigation Area Map III Nagari Singkarak.